PRINCIPLES OF ANTONYMOUS LEXEMIC COMBINATION IN INDONESIAN - I Dewa Putu Wijana (Diterbitkan oleh Jurusan Sastra Indonesia Fakultas Ilmu Budaya Universitas Jember bekerja sama dengan Himpunan Sarjana - Kesusastraan Indonesia (HISKI), Himpunan Pembina Bahasa Indonesia (HPBI) dan Masyarakat Linguistik Indonesia (MLI), 2023)
This article deals with Indonesian lexemic combination whose elements consisting of lexemes having antonymous meaning. By using data collected introspectively whose grammaticality and acceptability are tested with other Indonesian native speakers, it is found that the combinations are governed by three main principles, i.e. formal, semantic, and stylistic principles. The formal principle can further be classified into rhyming, phonological, and length principle. While, the semantic principle can be differentiated into marked, diametric and chronological, equity, idiomatic, and gender principle. Those principles seems to be hierarchical whose dominance has not been revealed in this research. Therefore, the more serious research concerning this matter is urgently needed.